Dynamic Handgrip Exercise: Feasibility and Physiologic Stress Response of a Potential Needle-Free Cardiac Magnetic Resonance Stress Test - Ochs, Andreas; Nippes, Michael; Salatzki, Janek; Weberling, Lukas D.; Riffel, Johannes; Müller-Hennessen, Matthias; Giannitsis, Evangelos; Osman, Nael; Stehning, Christian; André, Florian; Katus, Hugo A.; Frey, Norbert; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: CMR pharmacological stress-testing is a well-established technique for detecting myocardial ischemia. Although stressors and contrast agents seem relatively safe, contraindications and side effects must be considered. Substantial costs are further limiting its applicability. Dynamic handgrip exercise (DHE) may have the potential to address these shortcomings as a physiological stressor. We therefore evaluated the feasibility and physiologic stress response of DHE in relation to pharmacological dobutamine-stimulation within the context of cardiac magnetic resonance (CMR) examinations. Methods: Two groups were prospectively enrolled: (I) volunteers without relevant disease and (II) patients with known CAD referred for stress-testing. A both-handed, metronome-guided DHE was performed over 2 minutes continuously with 80 contractions/minute by all participants, whereas dobutamine stress-testing was only performed in group (II). Short axis strain by fast-Strain-ENCoded imaging was acquired at rest, immediately after DHE and during dobutamine infusion. Results: Eighty middle-aged individuals (age 56 ± 17 years, 48 males) were enrolled. DHE triggered significant positive chronotropic (HRrest: 68 ± 10 bpm, HRDHE: 91 ± 13 bpm, p < 0.001) and inotropic stress response (GLSrest: -19.4 ± 1.9%, GLSDHE: -20.6 ± 2.1%, p < 0.001). Exercise-induced increase of longitudinal strain was present in healthy volunteers and CAD patients to the same extent, but in general more pronounced in the midventricular and apical layers (p < 0.01). DHE was aborted by a minor portion (7%) due to peripheral fatigue. The inotropic effect of DHE appears to be non-inferior to intermediate dobutamine-stimulation (GLSDHE= -19.5 ± 2.3%, GLSDob= -19.1 ± 3.1%, p = n.s.), whereas its chronotropic effect was superior (HRDHE= 89 ± 14 bpm, HRDOB= 78 ± 15 bpm, p < 0.001). Conclusions: DHE causes positive ino- and chronotropic effects superior to intermediate dobutamine-stimulation, suggesting a relevant increase of myocardial oxygen demand. DHE appears safe and timesaving with broad applicability. The data encourages further studies to determine its potential to detect obstructive CAD.